(untitled) (Tanzania Medical Journal, 2010)
Background: Identification of obesity and other risk factors for cardiovascular disease in childhood is strongly recommended for prevention of the diseases in adulthood. Objectives: To determine the prevalence of the conventional cardiovascular risk factors among primary school children aged 6-15 years in Urban Dar es Salaam and Rural Morogoro. Methods: Anthropometric and blood pressure measurements were determined using standard techniques. Metabolic variables such asblood sugar, total cholesterol, low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol and triglycerides levels were assessed. A questionnaire was used to assess socio-demographic characteristics, involvement in physical activities and active and passive cigarette smoking. Results: Among the 508 studied children systolic hypertension was found in 11.4%, diastolic hypertension in 8.1% and combined hypertension in 3.9%. Obesity was observed in 5.3%. Four percent of the subjects were found to have elevated levels of total cholesterol and 2% elevated levels of LDL-cholesterol. Passive smoking was reported from 35%, while only 1.2% had a history of active cigarettesmoking. None had blood sugar levels that met the World Health Organisation’s definition of diabetes mellitus. Subjects from affluentfamilies were more likely to be hypertensive and obese. Most of thechildren were physically active. Conclusions: The prevalence of the conventional cardiovascular risk factors is relatively low among children in this society. A significant difference was, however, observed between children from different socio-economic backgrounds.Keywords: Cardiovascular risk factors, children, urban, rural